Benefit of extending the protocol for high resolution manometry according to the version 4.0 of the Chicago criteria. A multicenter study. Issue 3 (28th November 2022) - Alcalá‐González, Luis G.; Ezquerra‐Duran, Alberto; Aguilar, Ariadna; Barber, Claudia; Barba, Elizabeth; Araujo, Isis K.; Marin, Ingrid; Naves, Juan; Serra, Jordi
Abstract: Background: The last version of the Chicago Criteria for high resolution esophageal manometry proposes an expanded protocol including complementary maneuvers to improve the diagnostic yield of the exploration. Our aim was to determine the diagnostic gain of the CCv4.0 protocol compared to the CCv3.0 protocol. Methods: All manometry recordings performed in 4 reference centers during the first 10 months after the implementation of the new protocol were retrospectively reviewed. The time spent to complete the protocol was measured, and the changes in diagnosis resulting from the new CCv4.0 were compared to CCv3.0. Key Results: From a total of 756 HRM performed, 606 studies could be properly analyzed. The duration of the studies was 18.3 ± 4.3 min. From these, 11.3 ± 3.4 min were spent to complete the CCv3.0 protocol, and 7.4 ± 3.6 min were spent for the remaining maneuvers. A discordant diagnosis between CCv3.0 and CCv4.0 was obtained in 12% of patients: 32% of patients with ineffective esophageal motility turned to normal motility; 24% of patients with esophagogastric junction outlet obstruction (EGJOO) turned to a non‐obstructive disorder; and 1% of patients with an apparently normal EGJ relaxation, turned to an obstructive disorder. EGJOO according to CCv4.0 was more prevalent in patients referred for dysphagia (11%) than those referred for GERD (4%; p = 0.003). Conclusions and Inferences: Prolongation of the time spent to complete the CCv4.0 protocol leads to a change in the diagnosis of 12% of patients. Clinically relevant changes are mainly related to the evaluation of EGJOO. Abstract : The new protocol of HRM recommended by CC4.0. prolongs the exploration by 7 ± 4 min, and produces a change in the final diagnosis in 12% on patients, mainly an increment in normal motility, and a reduction in ineffective esophageal motility, and esophagogastric junction outlet obstruction.